The role of genetic polymorphisms in the thymidylate synthase (TYMS) gene in methotrexate-induced oral mucositis in children with acute lymphoblastic leukemia. Issue 10 (October 2018) - Oosterom, Natanja; Berrevoets, Marijn; den Hoed, Marissa A.H.; Zolk, Oliver; Hoerning, Susanne; Pluijm, Saskia M.F.; Pieters, Rob; de Jonge, Robert; Tissing, Wim J.E.; van den Heuvel-Eibrink, Marry M.; Heil, Sandra G.
Abstract : Objective: Methotrexate (MTX) is an important drug in the treatment of pediatric acute lymphoblastic leukemia (ALL). MTX is cytotoxic as it impairs DNA and RNA synthesis by inhibiting the enzymes dihydrofolate reductase ( DHFR ) and thymidylate synthase ( TYMS ). The association between genetic variants within the TYMS gene and MTX-induced toxicity has been studied, but results are inconsistent. We determined the role of three previously described variants within the TYMS gene and MTX-induced oral mucositis in a prospective cohort of Dutch children with ALL and performed a meta-analysis of the previous results. Materials and methods: We analyzed the presence of a 28-base pair tandem repeat (rs34743033; 2R3R), a single nucleotide polymorphism present within the 28-base pair repeat on the 3R allele (rs2853542; 3RG>C) and a 6-base pair deletion (rs15126436; TTAAAG) within the TYMS gene in germline DNA of 117 pediatric patients with ALL. Oral mucositis was defined as grade≥3 according to the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) v.3.0. Data were analyzed for the individual rs34743033 (2R3R) and rs151264360 (6 bp deletion) polymorphisms, whereas rs2853542 (3RG>C) was combined with rs34743033 (2R3R) and analyzed according to predicted expression levels of TYMS: low expression (2R/2R, 2R/3RC and 3RC/3RC), median expression (2R/3RG and 3RC/3RG) and high expression (3RG/3RG). We performed a meta-analysis of the current literature on these polymorphisms in relation to oral mucositis using a fixed effects model. Results: The 2R2R genotype (rs34743033) was not significantly associated with developing MTX-induced oral mucositis compared with the 2R3R/3R3R genotypes, which was confirmed in a meta-analysis [odds ratio (OR): 1.17 (0.62–2.19)]. Patients carrying the low-expression TYMS genotype (2R2R, 2R3RC, 3RC3RC) had an increased odds of developing MTX-induced oral mucositis [OR: 2.42 (0.86–6.80)], which did not reach statistical significance. The 6-bp deletion [rs151264360, OR: 0.79 (0.20–3.19)] was not associated with the development of MTX-induced oral mucositis. Conclusion: The TYMS 6-bp deletion and 2R3R polymorphism were not associated with MTX-induced oral mucositis. Validation studies in prospective cohorts are necessary to assess the possible role of the low-expression TYMS genotypes in relation to MTX-induced oral mucositis. Abstract : Supplemental Digital Content is available in the text.